2020
DOI: 10.1136/bmjsem-2019-000732
|View full text |Cite
|
Sign up to set email alerts
|

Can we improve coaches’ injury prevention views and implementation practices in the community female Gaelic sport of camogie?

Abstract: ObjectivesTo evaluate the effect of a nationwide coach education workshop on the attitudes towards, willingness and perceived ability of camogie coaches to implement a Camogie Injury Prevention Programme (CIPP) and their implementation of this programme 4 weeks after the workshop.MethodsCoaches (n=98) from all four provinces in Ireland were recruited and completed a questionnaire prior to and immediately following a developed workshop on the CIPP. Four weeks later 40 of the 98 coaches completed a follow-up que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Research on camogie and its players continues to grow in line with an increase in the sport's popularity, alongside players' reported time commitments and training regimes [1,2]. Previous research reported on players' injuries [2][3][4], strength and conditioning recommendations [1], and match-play demands [5,6]. Current match-play demand research has primarily focused on half-by-half comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Research on camogie and its players continues to grow in line with an increase in the sport's popularity, alongside players' reported time commitments and training regimes [1,2]. Previous research reported on players' injuries [2][3][4], strength and conditioning recommendations [1], and match-play demands [5,6]. Current match-play demand research has primarily focused on half-by-half comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…This accentuates the importance of a systematic IPP to decrease the severity of injuries [82]. An applied, minimally invasive example of an INT is the Gaelic specific injury prevention program (IPP) (GAA 15) [83][84][85]. Both…”
Section: Injury Incidence Risk and Preventionmentioning
confidence: 99%
“…In a self-reported participant injury survey in intercounty camogie, O'Connor et al (124) indicated that most traumatic injury that occurred in game activities was knee ligament (115,123). Therefore, strength & conditioning practitioners need to be cognizant that there is a high incidence of knee injuries in female field sports athletes (2).…”
Section: Injury Epidemiologymentioning
confidence: 99%
“…The strength & conditioning practitioner can play a pivot role in the education of both players and coaching staff. The implementation of an injury prevention program could assist in the potential reduction of injuries in hurling and camogie (49,123). (177).…”
Section: Injury Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation